Social Compact in Electricity Privatization in Southeastern Turkey : Building Dialogue and Consensus between the Citizens and the Electricity Company towards Improved Cost Recovery and Service - Darendeliler, Zeynep; Aydin, Cansu (World Bank, Washington, DC, 2015)
About 70 percent of electricity users in Southeastern Turkey are not used to paying for electricity, partially due to the protracted situation of conflict and lack of trust between citizens and the government in the region. Historic tension throughout the 1990s caused an inability for the government to invest in electricity infrastructure and has resulted in low service quality. A large portion of consumers did not pay for electricity use at all, since full electrification of these regions did not take place until the 1980s. This has also resulted in wasteful and non-sustainable patterns of electricity use behavior. The social compact pilot implemented in two provinces in this region, Mardin and Sanliurfa, set up stakeholder committees representing urban and rural communities to forge and sustain a dialogue between the consumers and the electricity company on increased electricity payment and improved service quality. The stakeholder committees came up with a joint stakeholder committee strategic plan to address payment, service quality and communication issues. Moving forward, the electricity company will institutionalize the stakeholder committee meetings, and start implementing portions of the strategic plan, starting with an energy efficiency educational campaign and improving its grievance redress mechanism. This is the beginning of a process to increase popular trust in and dialogue with formal institutions in a region marked by a protracted conflict and a deep distrust in the state and formal institutions.